Analysis of Critical Thinking Abilty Judging from Independent Learning and Learning with E-Module Assisted Flipped Classroom Model Material Changes in Form V - M. Amiril Mu'minin; YL. Sukestiyarno; AA Ketut Budiastra (Universitas Muhammadiyah Enrekang, 2024)
The purpose of this study was to improve students' learning independence and critical thinking skills in science in grade V on the material of changes in form through the flipped classroom model based on e-modules. Data analysis techniques were analyzed using quantitative analysis, namely one variable t-test, difference test, N-Gain test, and regression test, and then using qualitative analysis. The results of the study: (1) Students' critical thinking skills are more than the KKM value of 75 with the results of the calculated t value = 1.778 (> 1.706) and a significant value of 0.015 (<0.05); (2) There is an increase in students' critical thinking skills by 35.11% after learning with the flipped classroom model assisted by e-modules; (3) There is an influence of learning independence on students' critical thinking skills by 85.7% so that it can be concluded that the greater the students' learning independence, the higher the students' critical thinking skills.